Mentorship Programs for Faculty Development in Academic General Pediatric Divisions - Jennifer Takagishi; Sharon Dabrow (Hindawi Limited, 2011)
Introduction. Mentoring relationships have been shown to support academicians in areas of research, work/life balance, and promotion. Methods. General pediatric division chiefs accessed an electronic survey asking about mentorship relationships, their ability to create a mentorship program, and resources needed. Results. Dyadic mentorship programs were available at 53% of divisions. Peer mentorship programs were available at 27% of divisions. Overall, 84% of chiefs believed that dyadic mentorship would benefit their faculty. 91% of chiefs believed that peer mentorship would benefit their faculty. Chiefs were interested in starting peer (57%) or dyadic (55%) mentorship programs. Few divisions had a peer mentorship program available, whereas 24% already had a dyadic program. 43% of chiefs felt that they had the tools to start a program. Many tools are needed to create a program. Discussion. General pediatric division chiefs acknowledge the benefits of mentoring relationships, and some have programs in place. Many need tools to create them. Pediatric societies could facilitate this critical area of professional development.